Blood ties: migrations, state transnationalism and automatic nationality - Caggiano, Sergio (2017)
I propose contributing to the general understanding of the intricate relationship between nationality, citizenship and international migrations, focusing on the linkage or reincorporation policies of migrant-sending countries. Specifically, I will analyse a key change to the system for allocating Bolivian nationality by the Plurinational State of Bolivia and related measures during the presidency of Evo Morales, that is, the introduction of automatic jus sanguinis to maintain ties with emigrants. The automatic application of jus sanguinis abroad has theoretical implications on two different levels. One is the relationship between nationality and citizenship, specifically, that of the possible emancipation of citizenship from nationality. In this regard, the case I present reveals mechanisms that work in the opposite direction, binding citizenship to nationality. The second level is that of the potential expansion of ethno-nationalist or racialised conceptions of nationality.